Microbial community structure and function in sediments from e-waste contaminated rivers at Guiyu area of China. (April 2018) - Liu, Jun; Chen, Xi; Shu, Hao-yue; Lin, Xue-rui; Zhou, Qi-xing; Bramryd, Torleif; Shu, Wen-sheng; Huang, Li-nan
Abstract: The release of toxic organic pollutants and heavy metals by primitive electronic waste (e-waste) processing to waterways has raised significant concerns, but little is known about their potential ecological effects on aquatic biota especially microorganisms. We characterized the microbial community composition and diversity in sediments sampled along two rivers consistently polluted by e-waste, and explored how community functions may respond to the complex combined pollution. High-throughput 16S rRNA gene sequencing showed that Proteobacteria (particularly Deltaproteobacteria ) dominated the sediment microbial assemblages followed by Bacteroidetes, Acidobacteria, Chloroflexi and Firmicutes . PICRUSt metagenome inference provided an initial insight into the metabolic potentials of these e-waste affected communities, speculating that organic pollutants degradation in the sediment might be mainly performed by some of the dominant genera (such as Sulfuricurvum, Thiobacillus and Burkholderia ) detected in situ . Statistical analyses revealed that toxic organic compounds contributed more to the observed variations in sediment microbial community structure and predicted functions (24.68% and 8.89%, respectively) than heavy metals (12.18% and 4.68%), and Benzo (a) pyrene, bioavailable lead and electrical conductivity were the key contributors. These results have shed light on the microbial assemblages in e-waste contaminated river sediments, indicating a potential influence of e-waste pollution on the microbial community structure and function in aquatic ecosystems. Graphical abstract: Image 1 Highlights: River sediments from Guiyu were severely polluted by TOPs and heavy metals. Deltaproteobacteria dominated the sediment microbial assemblages. Some of the dominant genera might harbor pathways for TOPs degradation. TOPs contributed more to community structure and function than heavy metals. BaP, available lead and EC were the key contributors.